Implementing the Internal Control System in the Islamic Microfinance Institutions AN EXPLORATORY STUDY OF 13 BMT’S IN DEPOK CITY - Sepky Mardian; Rabitha Nabila Haifa (AHKAM : Jurnal Ilmu Syariah, 2015)
BMT (Bayt al-Mal wa al-Tamwil) should further improve the prudential principles in giving credit to avoid things that are unintended. Therefore, it needs to improve the internal control system (ICS), so the risk of financing problems can be prevented. This study refers to the internal control system based on the COSO framework. The object of this study is 13 BMTs in Depok. The study found that the internal control system at 13 BMTs in Depok were effective. This is supported by the results of the answers to the questionnaire related to 86% effectiveness of internal controls. However, it is still found weaknesses in the lack of spontaneous checks on the use of funds by customers, incompleteness flowchart and pre-numbered documentsDOI: 10.15408/ajis.v15i2.2863